2017
DOI: 10.1186/s12870-017-1019-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to trace amounts of sulfonylurea herbicide tribenuron-methyl causes male sterility in 17 species or subspecies of cruciferous plants

Abstract: BackgroundFor most cruciferous plants, which are known as important crops and a number of weeds, hybrid breeding is hampered by the unavailability of a pollination control system. Male sterility induced by a gametocide can be useful for the utilization of plant heterosis.ResultsThe gametocidal effect of sulfonylurea herbicide tribenuron-methyl was tested across seventeen cruciferous species or subspecies including Brassica juncea, B. carinata, B. oleracea ssp. capitata, B. oleracea ssp. acephala, B. rapa ssp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Some previous evidences suggested that valine, leucine and isoleucine may be involved in the regulation of cell division (Rost et al, 1990 ) and sulfonylurea herbicides disturbed cell division in the meristematic tissues of plants (Saja et al, 2016 ). We also found that amidosulfuron can restrain the raceme elongation (cell growth) in the first days after treatment and the pollen development was terminated before microspore mitosis (the flower bud length of 3–3.5 mm), as various sulfonylurea herbicides did in different cultivars (Yu et al, 2006 , 2009 , 2017 ; Yu and He, 2014 ; Li et al, 2015 ). The increase of endogenous ethylene in the treated plants may cause frustration on plant growth and development including cell cycle.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some previous evidences suggested that valine, leucine and isoleucine may be involved in the regulation of cell division (Rost et al, 1990 ) and sulfonylurea herbicides disturbed cell division in the meristematic tissues of plants (Saja et al, 2016 ). We also found that amidosulfuron can restrain the raceme elongation (cell growth) in the first days after treatment and the pollen development was terminated before microspore mitosis (the flower bud length of 3–3.5 mm), as various sulfonylurea herbicides did in different cultivars (Yu et al, 2006 , 2009 , 2017 ; Yu and He, 2014 ; Li et al, 2015 ). The increase of endogenous ethylene in the treated plants may cause frustration on plant growth and development including cell cycle.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, obtention of highly efficient gametocides is the first task in a breeding scheme using CIMS. Some herbicides that inhibit acetolactate synthase (ALS; EC 4.1.3.18), such as tribenuron-methyl (Express) and amidosulfuron (Hoestar/Gratil), were showed to be able to induce complete male sterility in many cruciferous species when they were applied at trace amounts (about 1% dosage recommended for weed control; Yu et al, 2006 , 2009 , 2017 ; Yu and He, 2014 ; Li et al, 2015 ). In the last decade, over 20 commercial hybrid rapeseed varieties based on CIMS have been registered in China, for examples, Shaanyou1209, Zhongyouza19, Qinyou33, and Yuhuang1.…”
Section: Introductionmentioning
confidence: 99%
“…Some chemicals have been reported as CHAs for hybrid seeds production in rapeseed ( Guan, 2014 ; Yu and He, 2014 ). A few of sulfonylurea herbicides, which are a class of the most widely used acetohydroxyacid synthase (AHAS, EC 2.2.1.6)-inhibiting herbicides, can induce complete male sterility in rapeseed at a concentration less than 1% of that required for their herbicide activity, such as tribenuron methyl (TBM) ( Yu et al, 2006 ; Zhang et al, 2010 ; Yu et al, 2017 ), monosulfuron-ester sodium ( Cheng et al, 2013 , 2015 ; Li Z. et al, 2015 ), and amidosulfuron ( Yu et al, 2009 ). So far, several dozens of commercial rapeseed ( B. napus ) hybrids based on male sterility induced by TBM or other sulfonylurea herbicides have been registered in China ( Cheng et al, 2013 ; Yu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the application of some sulfonylurea (SU) herbicides, such as tribenuron-methyl (TBM) [19] and amidosulfuron [20], had a strong gametocidal effect on OSR and allowed the treated plants to outcross. These SUs have been validated as useful gametocides for OSR and other Brassica species, and now, their different forms have been widely used by many institutes and seed companies in China [21]. More than 20 commercial hybrids based on SU gametocides have been released in China [21] by OSR breeders from Shaanxi, Hubei, Chongqing, Hunan, Sichuan, Jiangsu, Zhejiang, and Jiangxi provinces.…”
Section: Introductionmentioning
confidence: 99%
“…These SUs have been validated as useful gametocides for OSR and other Brassica species, and now, their different forms have been widely used by many institutes and seed companies in China [21]. More than 20 commercial hybrids based on SU gametocides have been released in China [21] by OSR breeders from Shaanxi, Hubei, Chongqing, Hunan, Sichuan, Jiangsu, Zhejiang, and Jiangxi provinces. SU herbicides target the acetolactate/acetohydroxylate synthase (ALS/ AHAS) enzyme, which is a key enzyme in the biosynthesis of valine, leucine, and isoleucine.…”
Section: Introductionmentioning
confidence: 99%